Lives of lesbian elders : looking back, looking forward - Clunis, D. Merilee (Routledge, 2012)
The untold history of lesbian life from those who have lived it! Lives of Lesbian Elders: Looking Back, Looking Forward illuminates the hopes, fears, issues, and concerns of gay women as they grow older. Based on interviews with 62 lesbians ranging in age from 55 to 95, this very special book provides a historical account of the shared experiences of the lesbian community that is so often invisible or ignored in contemporary society. The book gives voice to their thoughts and feelings on a wide range of issues, including coming out, identity and the meaning of life, the role of family.